2017
DOI: 10.1242/dev.150680
|View full text |Cite
|
Sign up to set email alerts
|

Multiple modes of Lrp4 function in modulation of Wnt/β-catenin signaling during tooth development

Abstract: During development and homeostasis, precise control of Wnt/β-catenin signaling is in part achieved by secreted and membrane proteins that negatively control activity of the Wnt co-receptors Lrp5 and Lrp6. Lrp4 is related to Lrp5/6 and is implicated in modulation of Wnt/β-catenin signaling, presumably through its ability to bind to the Wise (Sostdc1)/sclerostin (Sost) family of Wnt antagonists. To gain insights into the molecular mechanisms of Lrp4 function in modulating Wnt signaling, we performed an array of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 48 publications
3
61
0
1
Order By: Relevance
“…Previous studies have revealed that SOST has anti‐anabolic effects on bone formation . Recently, it has been reported that SOST is closely associated with the development of dental tissues . For example, SOST inhibition dramatically stimulates alveolar bone regeneration following experimental periodontitis in Sprague‐Dawley (SD) rats .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that SOST has anti‐anabolic effects on bone formation . Recently, it has been reported that SOST is closely associated with the development of dental tissues . For example, SOST inhibition dramatically stimulates alveolar bone regeneration following experimental periodontitis in Sprague‐Dawley (SD) rats .…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, it has been reported that SOST is closely associated with the development of dental tissues. [6][7][8][9] For example, SOST inhibition dramatically stimulates alveolar bone regeneration following experimental periodontitis in Sprague-Dawley (SD) rats. 6 Another report has demonstrated that SOST inhibition resulted in significant new deposition of cellular cementum and the formation of well-organized periodontal ligament fibre in a rat periodontal defect model.…”
Section: Introductionmentioning
confidence: 99%
“…Комплекс Wnt посредством аппарата Гольджи секретируется во внекле-точную среду, где он выступает важным участником процесса межклеточной передачи сигналов. Рецепторами Wnt выступают трансмембранные белки Frizzled и рецепторы липопротеинов LRP4, LRP5, LRP6 [41]. Ген локализован на хромосоме 11p11.2.…”
Section: Apoe-c1-c2-c4unclassified
“…To date, three Wnt signaling pathways have been revealed, including the canonical Wnt/β-catenin pathway, the noncanonical Wnt/Ca 2+ pathway, and the Wnt/planar cell polarity (PCP) pathway [11]. The canonical Wnt/β-catenin pathway plays an important role in the regulation of bone formation and has become a new hotspot in the field of the pathogenesis of skeletal diseases and bone metabolism [12,13]. However, little is known about whether a Wnt/β-catenin signaling pathway could promote ectopic bone formation induced by HA/β-TCP biomaterials through exercise and immunoregulation in mice.…”
Section: Introductionmentioning
confidence: 99%